2021
DOI: 10.1186/s12891-021-04489-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between full-thickness degenerative supraspinatus tear and radiographic parameters including the acromiohumeral centre edge angle and the greater tuberosity angle

Abstract: Background Many radiographic parameters associated with the extrinsic cause of supraspinatus tears have been proposed. The aim of this study was to assess the relationship between a full-thickness degenerative supraspinatus tear (FTDST) and the patient’s radiographic parameters, including the acromiohumeral centre edge angle (ACEA) and the greater tuberosity angle (GTA). Methods A retrospective study was conducted. We included 116 patients who unde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…A classical predictor, the GTA, was created in 2018 and a mean value of 70 -72° signi cantly associated with developing a RCT. 10,23 In our study, the mean values of GTA were 70.15° in the RCT group and 64.75° for the control, comparable to the previous ndings. DRR is another practical parameter to diagnose and predict RCT with a value over 1.38 considered as a risk factor of having a RCT, 11 which was in accordance with our results in the present study.…”
Section: Comparison Of Predictors Between Groupssupporting
confidence: 91%
See 1 more Smart Citation
“…A classical predictor, the GTA, was created in 2018 and a mean value of 70 -72° signi cantly associated with developing a RCT. 10,23 In our study, the mean values of GTA were 70.15° in the RCT group and 64.75° for the control, comparable to the previous ndings. DRR is another practical parameter to diagnose and predict RCT with a value over 1.38 considered as a risk factor of having a RCT, 11 which was in accordance with our results in the present study.…”
Section: Comparison Of Predictors Between Groupssupporting
confidence: 91%
“…18 A similar dilemma was observed in the GTA, as it signi cantly differed between groups but failed to be eligible for a predictor of full-thickness degenerative supraspinatus tear. 23 In our study, the AI and the GTA were both quali ed as independent risk factors, but their predictive abilities were a little weaker, only increasing the odd of having a RCT by approximately three folds. An appropriate improvement to increase their detectability was necessary in the situation.…”
Section: Predictive Abilitymentioning
confidence: 45%
“…[26][27][28][29][30] This evidence pointed out that surgical treatment such as subacromial decompression and acromioplasty may not be so effective in treating RCTs, and the intrinsic factors might be the main reason of RCTs. However, we should not deny the significant differences found in anatomic structures between the RCT group and the control group, for example, the differences in the acromion index (AI), the CSA and the GTA, which have been reported in many literatures 10,15,16,[31][32][33] and support the mechanism of extrinsic factors. In our perspective, because the DRR was found significantly larger in shoulders with RCTs, we acknowledge the extrinsic factor as a contributor to RCTs.…”
Section: Clinical Recommendationmentioning
confidence: 98%
“…In Pandey et al’s research, they found a significant difference in the value of AI between the full-thickness RCT group and the control group, but the stepwise logistic regression rejected the AI as a predictor for the occurrence of a RCT [ 13 ]. A similar dilemma was observed in the GTA, as it significantly differed between groups but failed to be eligible for a predictor of full-thickness degenerative supraspinatus tear [ 18 ]. In our study, the AI and the GTA were both qualified as independent risk factors, but their predictive abilities were a little weaker, only increasing the odd of having a RCT by approximately three folds.…”
Section: Discussionmentioning
confidence: 88%
“…Unlike CSA and AI, the impact of the superolateral extension of the greater tuberosity on the development of RCT was just recognized in recent years. A classical predictor, the GTA, was created in 2018 and a mean value of > 70—72° significantly associated with developing a RCT [ 5 , 18 ]. In our study, the mean values of GTA were 70.15° in the RCT group and 64.75° for the control, comparable to the previous findings.…”
Section: Discussionmentioning
confidence: 99%